Comparison of wellbore stability of UBD in the case of laser drilling and conventional operation - Bazargan, M. (EAGE Publishing BV, 2014)
In recent years, growing interest in underbalanced drilling has resulted in the rapid development of its associated equipment technology, practices, and procedures. Underbalanced drilling is used to avoid lost circulation, formation damage, and decreasing weight on bit. However, the risk of wellbore collapse due to lake of hydrostatic mud pressure is high; therefore, using good geo-mechanical model may avoid wellbore instability problems. In order to evaluate the potential for wellbore instability, it is necessary to use an elastoplastic model to compute the stresses and strains around the bore hole. Furthermore, it should be mentioned that the laser drilling process depends extremely on the rock's geo-mechanical properties. This paper describes a numerical investigation of wellbore instability in a fractured carbonate reservoir that is verified with reservoir core samples. Some necessary conditions should be mentioned to gain the best method of comparison for conventional UBD and laser UBD operations. It is vital to evaluate the sensitivity of the wellbore stability by focusing on the effect of laser irradiation absorption. Finally, this paper fills the gap by paying attention to the sensitivity analysis and focuses on assessing the influence of various drilling methods, rock properties and optical fluid parameters.